(A-B)U(B-A) IN SETS.
Answers
Answered by
1
Let A={a,b,c} & B={a,b,d}
LHS=> A-B={c} and B-A={d}
Thus, (A-B) U (B-A)={c,d}
RHS=> A U B= {a,b,c,d}
A ∩ B = {c,d}
Thus, (A U B) - (A ∩ B) = {c,d}
LHS=RHS
Hope it helps.
LHS=> A-B={c} and B-A={d}
Thus, (A-B) U (B-A)={c,d}
RHS=> A U B= {a,b,c,d}
A ∩ B = {c,d}
Thus, (A U B) - (A ∩ B) = {c,d}
LHS=RHS
Hope it helps.
Answered by
0
Hi i hope it helps you
Attachments:
![](https://hi-static.z-dn.net/files/dd8/79adfe0e26e7c8cc005d3818f16f0c73.jpg)
Similar questions
Social Sciences,
8 months ago
Biology,
1 year ago
Biology,
1 year ago
Art,
1 year ago
Social Sciences,
1 year ago